Systems Measures of a Trauma-Informed Approach: A Systematic Review - Champine, Robey B. (Am J Community Psychol, 2019)
Interest in trauma-informed approaches has grown substantially. These approaches are characterized by integrating understanding of trauma throughout a program, organization, or system to enhance the quality, effectiveness, and delivery of services provided to individuals and groups. However, variation in definitions of trauma-informed approaches, coupled with underdeveloped research on measurement, pose challenges for evaluating the effectiveness of models designed to support a trauma-informed approach. This systematic review of peer-reviewed and grey literature identified 49 systems-based measures that were created to assess the extent to which relational, organizational, and community/system practices were trauma-informed. Measures were included if they assessed at least one component of a trauma-informed approach; were not screening or diagnostic instruments; were standardized; were relevant to practices addressing the psychological impacts of trauma; were printed in English; and were published between 1988 and 2018. Most (77.6%) measures assessed organizational-level staff and climate characteristics. There remain several challenges to this emerging field, including: inconsistently reported psychometric data; redundancy across measures; insufficient evidence of a link to stakeholder outcomes; and limited information about measurement development processes. We discuss these opportunities and challenges and their implications for future research and practice.